A.B. Dyer papers - Dyer, A. B. (Alexander Brydie), 1852-1920.; Dyer, Alexander B. (Alexander Brydie), 1815-1874.
Chiefly records of the 4th Regiment, U.S. Artillery, in the Mexican and Civil War periods, with copies of orders, maps, and a history of the regiment, 1789-1847, with notes and sketches to 1877. Also includes a journal, 1844-1845, kept by Lt. Alexander B. Dyer stationed at the U.S. Army arsenal, St. Louis, Mo.
U.S. Army officer.
Collection material in English.
Keywords: United States. -- Army -- Officers; United States. -- Army. -- Artillery Regiment, 4th.; Fortification -- Missouri -- Saint Louis; Mexican War, 1846-1848.; Military bases -- Missouri -- Saint Louis; Regimental histories; United States -- History -- Civil War, 1861-1865.; Army officers